2007
DOI: 10.1111/j.1442-2042.2006.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral fused pelvic kidney ectopia with a single draining ureter solved by craniolateral displacement of the kidney and Boari‐modified bladder–calyceal anastomosis with bladder augmentation

Abstract: Abstract:A pelvic cake kidney with hydronephrosis and renal failure with the single draining ureter was reported. Frequent urination related to compression of the bladder was the most important symptom. The kidney was craniolaterally displaced , the malfunctioning ureter was replaced with the Boari-like tubularization of the bladder, and the neoureter was anastomosed with the calyx. The bladder was enlarged by intestinal augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
1
Order By: Relevance
“…Although our finding of early expression peak of SMARCAL1, as well as localization in metanephric mesenchymal cells and in Wilms' tumor (early defect of nephrogenesis), correlates with the presence of renal malformation (crossed fused ectopic kidney) in the index patient, this phenotype has not been previously reported in SIOD and may represent an incidental finding. Indeed, the population incidence of renal ectopia, encompassing crossed fused ectopia, is approximately 1 in 10,000 patients, and in different autopsy series it is detected in 1 in 1,000 to 1 in 7,000, which is higher than SIOD (15). Nevertheless, we suggest this finding, which might have been overlooked in the past as part of the renal phenotype of SIOD.…”
Section: Discussioncontrasting
confidence: 48%
“…Although our finding of early expression peak of SMARCAL1, as well as localization in metanephric mesenchymal cells and in Wilms' tumor (early defect of nephrogenesis), correlates with the presence of renal malformation (crossed fused ectopic kidney) in the index patient, this phenotype has not been previously reported in SIOD and may represent an incidental finding. Indeed, the population incidence of renal ectopia, encompassing crossed fused ectopia, is approximately 1 in 10,000 patients, and in different autopsy series it is detected in 1 in 1,000 to 1 in 7,000, which is higher than SIOD (15). Nevertheless, we suggest this finding, which might have been overlooked in the past as part of the renal phenotype of SIOD.…”
Section: Discussioncontrasting
confidence: 48%
“…The injury may necessitate the removal of the ectopic kidney [1]. Ignjatovic et al [9] also suggested that surgery in ectopic kidneys, if performed, should be done only once and should preferably be a nephrectomy. On the other hand, there are occasional reports of such injuries being managed conservatively [10].…”
Section: Discussionmentioning
confidence: 99%